2016
DOI: 10.1007/s10517-016-3414-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Afobazole and Betaine on Cognitive Disorders in the Offspring of Rats with Streptozotocin-Induced Diabetes and Their Relationship with DNA Damage

Abstract: Cognitive activity in 60-day-old offspring of rats (intrauterine development in experimental streptozotocin-induced diabetes) was studied on the model of food-seeking behavior under conditions of free choice in a 6-arm maze. The formation of the food-procuring skill was significantly delayed, which attests to impairment of cognitive functions in these animals. Peroral administration of afobazole (10 and 50 mg/kg) and betaine (50 and 100 mg/kg) significantly and dose-dependently alleviated this disorder. Correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…It is interesting to report that Bet restored DNA in the ilium and caused a partial recovery in the jejunum DNA [66]. Bet, as a methyl donor group, increases the methionine and/or cysteine for glutathione synthesis that protects the cell from ROS and reaction metabolites, and boosts the synesthesia of DNA [17,67].…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to report that Bet restored DNA in the ilium and caused a partial recovery in the jejunum DNA [66]. Bet, as a methyl donor group, increases the methionine and/or cysteine for glutathione synthesis that protects the cell from ROS and reaction metabolites, and boosts the synesthesia of DNA [17,67].…”
Section: Discussionmentioning
confidence: 99%
“…Though it remains to be tested directly, cognitive deficits observed in patients with type-2 diabetes may be a result of homocysteine neurotoxicity/neurodegeneration since dysregulation of betaine is observed in patients with obesity and diabetes (Lever et al, 2012;McEntyre et al, 2015). Furthermore, 10.3389/fnins.2023.1214976 therapeutic application of betaine in offspring following exposure to induced diabetes in utero demonstrated promising preservation of cognitive function (Zabrodina et al, 2016). In sum, betaine offers neuroprotection under conditions of both osmotic and metabolic stress given its dual role as an osmolyte and as a methyl donor.…”
Section: Neuroprotective Properties Of Betaine As a Methyl Donormentioning
confidence: 99%
“…In this way, it fulfills 3 functions: reduction of homocysteine, an increase of methionine for protein synthesis, and production of SAM (S-adenosylmethionine) which is a universal donor of methyl groups for several metabolic functions contributing to homeostasis. At least 10 studies to date [33][34][35][36][37][38][39][40][41][42] have shown cardiovascular benefits in betaine supplemented compared to controls.…”
Section: Role Of Creatine and Creatine Precursors Supplementation On ...mentioning
confidence: 99%